Prevalence, Pathophysiology, and Treatment of Urticaria post-COVID-19 Vaccination: A Systematic Review - Nugrahaeni, Ardhina; Budiyanti, Rani Tiyas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2023)
Background: Vaccination for COVID-19 has been intensively developed since the end of 2020. Its use must also obtain an Emergency Use Authorization (EUA) permit. Some of the vaccines have been used including Sinovac, Astra Zeneca, Moderna, Pfizer, Johnson & Johnson, and Sinopharm. In fact, there are many effects that have developed after the COVID-19 vaccination administration like local reactions, systemic reactions, and other reactions. In addition, one of them is urticaria. However, the existing literature has focused poorly on urticaria caused by COVID-19 vaccines. Aims: This research explores the prevalence, pathophysiology, and treatment of urticaria post-COVID-19 vaccination. Methods: This study conducted a systematic review based on the guideline which is Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We searched Scopus, ProQuest, Ebsco, and Google Scholar databases from 2020 until 2022 for identifying the data regarding urticaria post-COVID-19 vaccination. In a nutshell, 9 studies were included in the systematic review. Results: Only 28% of urticarial rashes incident among all cutaneous adverse reactions after post-COVID-19, it was higher among females and people aged 45-49 years old, and people with allergy histories. The most frequent reaction is urticarial following the COVID-19 vaccine administration. This concerns hypersensitivity reaction related to Immunoglobulin E (IgE) mediated, Immunoglobulin G (IgG), and sensitizing excipients in COVID-19 vaccines. Conclusion: This systematic review raises the concern of hypersensitivity reaction that related to IgE-mediated, IgG, and sensitizing excipients in COVID-19 vaccines. Urticaria is the most frequent reaction after the COVID-19 vaccine administration. Attention to medical history and immunology/allergy consultation might be advantageous to assess the risk of allergy and the guidance of the vaccine. Received: 9 May 2023; Revised: 8 June 2023; Accepted: 18 July 2023